TINJAUAN YURIDIS PRAKTEK PEMBUATAN AKTA NOTARIS DALAM HAL PENGHADAP MENGHADAP DALAM KURUN WAKTU DAN TEMPAT YANG BERBEDA - Anny Mawartiningsih; Maryanto Maryanto (Jurnal Akta, 2017)
Research on "Judicial Review of the Practice of Notarial Deed Making in the Facing Facing in Different Time and Place" aims to know and analyze the provisions or rules in authentic deed making by Notary in accordance with the applicable Law, the practice of making the deed in the case of confronting facing in, different time and place, and the validity of deeds made in, respects in different times and places. The approach of this study is sociological jurisdiction and data collection through literature study, observation and interview. Data analysis is done qualitatively.The provisions or rules in the authentic deed making by a notary shall in essence comply with the provisions of Articles 1867 and 1868 of the Civil Code, that authentic deeds as written evidence in the form as prescribed by law shall be made by or in the presence of a notary publicly authorized to manufacture an authentic deed in the place where the deed is made. In the making of authentic deed by the notary, the legislation referred to is the Law of Position Notary (UUJN). This is in accordance with the provisions of Article 1 to 7 of Law Number 2 Year 2014 concerning Amendment to Law Number 30 Year 2004 concerning Notary Position stating that the Notary Deed hereinafter referred to as Deed is an authentic deed made by or in the presence of Notary by form and procedures specified in the Law of Notary (UUJN). The practice of making the deed in the case of face-facing, different time and place occurs because of the reason for its practicality due to the limited time confrontation and / or the existence of the interest that can not be abandoned. In addition to the mutual trust of the parties so that hand over the aktanya management to other parties. The validity of a deed made in respect of faces facing different times and places is authenticated as an authentic deed as long as the deed is made in a notarial position and read and signed in the presence of the parties with at least two witnesses present, unless the parties wish the acts are not read out. If it is not met or the signing is done in different time and place then the deed has legal force as deed under the hand.Keywords: Notarial Deed, Encounter, Time and Place